Model integrated evidence approach for rational and safe formulation development: case of alfuzosin prolonged-release tablets - Sivacharan Kollipara, Rajkumar Boddu, Suribabu Bonda, Hariharan Venugopal, Chandra Deb, Pavan Kumar Mittapalli, Anand Arumugam, Sohel Mohammed Khan, Venkat Ramana Naidu (Journal of Applied Pharmaceutical Science, 2025)
The model integrated evidence (MIE) approach aims to utilize simulation tools like physiologically based biopharmaceutic model (PBBM) or physiologically based pharmacokinetic (PBPK) model for the development of new drugs and generic formulations. In the current case, MIE is utilized for developing rational and safe formulations for alfuzosin prolonged-release tablets. Due to the side effects of postural hypotension, it is required to develop a formulation that can have lesser yet bioequivalent Cmax. To support this, the PBBM model was developed using physicochemical, disposition, and dissolution data in 0.01N HCl and pH 4.5 acetate buffer. The model was validated using literature reported in vitro in vivo correlation. Bioequivalence predictions indicated that in-house generic formulation is bioequivalent to reference and thus enabled direct pivotal study. The outcome from the pivotal bioequivalence study yielded Cmax T/R ratio, although lower (by 13%) it is bioequivalent to the reference formulation. The results matched with predictions and demonstrated the significance of MIE in formulation development. Comparison of generic formulation with other brands A, B, and C indicated that generic formulation is superior over others in terms of in vitro similarity and in vivo bioequivalence. Overall, this work signifies the novel use of MIE in rational formulation development that can reduce the expensive human clinical studies and enable faster approvals.
Keywords: Model integrated evidence (MIE), Prolonged release, PBBM, Gastroplus, Bioequivalence, Dissolution